Effect of deficit irrigation and methyl jasmonate application on the composition of strawberry (Fragaria x ananassa) fruit and leaves - Giné-Bordonaba, Jordi; Terry, Leon A. (Elsevier, 2015)
Drought stress is among the most severe environmental risks threatening strawberry production. In the present study, the effect of deficit irrigation (DI; 50 mL/day) and/or elicitation with methyl jasmonate (MeJA; 0.1 mM) on the composition of secondary fruit and leaves from three strawberry pre-commercial cultivars (253/29, 279/4 and 279/5) was investigated and compared to plants kept at or near field capacity (200 mL/day). For certain cultivars (253/29), DI applied at green stage of fruit development resulted in a considerable reduction in berry size (1.7-fold). In other cultivars (279/4 and 279/5), fruit size was comparable in DI-treated and fully irrigated plants. Changes in the major sugars and organic acids of strawberry leaves and fruit were cultivar and organ dependent and were associated to an osmotic adjustment strategy within the plant to counteract the effects of drought. Overall, elicitation with MeJA had a minimal effect on plant growth and morphological traits. Nevertheless, MeJA increased fructose content of DI-treated leaves and palliated the differences in glucose content of fruit from different water treatments. The most pronounced effect of MeJA was related to an enchance synthesis and accumulation of pelargonidin-3-glucoside (nearly 2-fold) in red-ripe fruit from cultivar 279/5.
Keywords: Anthocyanins; Berry size; Drought; Organic acids; Sugars